Two Stages Splicing System - Mudabera, Mohammad Hassan; Yuhani, Yusof (2014)
The study of the biological process of deoxyribonucleic acid (DNA) splicing system in a translucent approach was investigated in 2012 by Yusof under the framework of formal language theory. In this work, the concepts of splicing system in two stages as well as splicing languages are mathematically and biologically discussed. Additionally, some theorems based on recognition site factor of initial strings at the existence of two initial strings and two rules are provided via Yusof-Goode (Y-G) approach. Besides, an example is also given in showing the biological meaning of the introduced concept.